Numerical determination of NN potential depth for a deuteron nucleus (Texas Journal of Multidisciplinary Studies, 2022)
Determining the potential depth of NN bound nuclei is important for determining the wave function of these nuclei. In particular, when determining the probability of the occurrence of nuclear reactions, the effective cross section and the reaction rate, it is necessary to know the wave function of the nuclei participating in this reaction. In this paper, we determined the depth of the NN potential of the deuteron nucleus (for Gaussian and exponential potentials) numerically using the wolfram mathematica software package.